IMPLICATIONS OF USING GRAB FOOD APPLICATIONS ON CONSUMER SATISFACTION - Rahman, Abdul; Sukmawardani, Ami; Fahiran, M. Nodia Arza (Transpublika Publisher, 2022)
The emergence and explosion of the internet in this technological era has provided an online business platform for services and products. One of them is the food delivery industry. Online food delivery is a service that allows customers to purchase food from a website or mobile app and have it delivered to their home. This study aims to determine and explain the effect of purchasing experience on customer trust and customer satisfaction with Grab Food customers. The choice of location for this research considers that customers who usually buy food using Grab Food are customers whose market segments are in large urban communities. The exogenous variable in this study is the buying experience, while the endogenous variable is customer trust and satisfaction. This study provides insight into customer satisfaction with mobile food delivery apps from the new norm of a COVID-19 scalable perspective. The quality of the application website and the convenience of using the application are revealed as important factors that significantly affect customer satisfaction during the pandemic.